WHAT TESTOSTERONE CONCENTRATIONS SHOULD WE EXPECT IN HEALTHY MEN? - Yeap, Bu Beng (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Older men generally have lower testosterone concentrations compared with younger to middle-aged men. In aging men, lower testosterone concentrations are associated with poorer health outcomes. Understanding the relationship between testosterone and men’s health status has implications for defining appropriate testosterone reference ranges to apply in clinical practice. METHODOLOGY Studies defining reference ranges for testosterone in selected groups of healthy men and meta-analyses of prospective cohort studies which analysed associations of testosterone with key health outcomes in community-dwelling men were identified. These studies used mass spectrometry to assay testosterone concentrations. RESULTS In 124 men aged 21-35 years with normal reproductive function, 95% confidence limits for testosterone were 10.4- 30.1 nmol/L. In 1185 non-obese men aged 19-39 years, the range was 9.2-31.8 nmol/L. In 394 healthy men aged 70-89 years, the range was 6.4-25.7 nmol/L. Individual participant data (IPD) meta-analyses of 21,074 men from nine studies showed lower testosterone concentrations in men older than 70 years (with higher luteinising hormone), and in those with higher BMI, or with diabetes or cancer. Extension of these IPD meta-analyses showed non-linear associations of testosterone with all-cause and cardiovascular mortality risk. Men with low testosterone concentrations (<7.4 nmol/L) had higher all-cause mortality. CONCLUSION Reference ranges for testosterone in healthy younger to middle-aged men are higher than for healthy older men. Leydig cell impairment is apparent in men older than 70 years. Age >70 years, BMI, and presence of ill-health need to be considered when interpreting testosterone results. Testosterone concentrations expected in healthy men can also be defined by thresholds below which risks of poorer health outcomes, such as mortality, increase.